A Galvanic Sensor for Monitoring the Corrosion Condition of the Concrete Reinforcing Steel: Relationship Between the Galvanic and the Corrosion Currents - Pereira, Elsa Vaz (Molecular Diversity Preservation International (MDPI), 2009)
This work reports a study carried out on the design and performance of galvanic and polarization resistance sensors to be embedded in concrete systems for permanent monitoring of the corrosion condition of reinforcing steel, aiming to establish a correlation between the galvanic currents, I(gal), and the corrosion currents, I(corr), estimated from the polarization resistance, R(p). Sensors have been tested in saturated Ca(OH)(2) aqueous solutions, under a variety of conditions, simulating the most important parameters that can accelerate the corrosion of concrete reinforcing steel, such as carbonation, ingress of chloride ions, presence or absence of O(2). For all the conditions, the influence of temperature (20 to 55 °C) has also been considered. From this study, it could be concluded that the galvanic currents are sensitive to the various parameters following a trend similar to that of the R(p) values. A relationship between the galvanic and the corrosion current densities was obtained and the limiting values of the I(gal), indicative of the state condition of the reinforcing steel for the designed sensor, were established.